Analisis Pengaruh Pemberiaan Ektrak Rimpang Jahe (Zingiber Officinale Rosc.) terhadap Gambaran histolopatologi islet panckreas Pada Tikus wistar Model Hiperglikemia: Sebuah Studi Preklinis - Setiawan, Bela Bagus; Tursinawati, Yanuarita; Widianingrum, Rifka (Jurnal sosial dan sains, 2025)
Diabetes mellitus (DM) is a metabolic disease with increasing prevalence in Indonesia. Melatonin is known to have promising antioxidant and antidiabetic properties. Ginger (Zingiber officinale Rosc.) contains higher melatonin content compared to other spices. To identify the effect of melatonin-rich ginger rhizome extract on blood glucose levels in hyperglycemic rats induced by STZ-NA. True experimental study with Pre Test Post Test Control Group Design using 30 male Wistar strain rats divided into 5 groups: negative control (K-), positive control (K+), ginger extract 100 mg treatment (P1), ginger extract 200 mg treatment (P2), and metformin positive control (P3). Hyperglycemia was induced with STZ-NA, then treated for 21 days. Blood glucose levels were measured using GOD-PAP method. There were significant differences in islet of Langerhans histopathology between groups (p=0.001). The K(-) group showed normal conditions (mean Allred: 4.6), while K(+) experienced severe necrosis (mean Allred: 2.32). The P2 group showed the best improvement (mean Allred: 4.8), followed by P3 (3.9) and P1 (3.72). Melatonin-rich ginger rhizome extract has protective effects against islet of Langerhans histopathological damage in hyperglycemic rat models, with 200 mg dose showing the best effectiveness.